Epoxyazadiradione suppresses breast tumor growth through mitochondrial depolarization and caspase-dependent apoptosis by targeting PI3K/Akt pathway - Kumar, Dhiraj; Haldar, Saikat; Gorain, Mahadeo; Kumar, Santosh; Mulani, Fayaj A.; Yadav, Amit S.; Miele, Lucio; Thulasiram, Hirekodathakallu V.; Kundu, Gopal C. (BMC Cancer, 2018)
Background: Breast cancer is one of the most commonly diagnosed invasive cancers among women around the world. Among several subtypes, triple negative breast cancer (TNBC) is highly aggressive and chemoresistant. Treatment of TNBC patients has been challenging due to heterogeneity and devoid of well-defined molecular targets. Thus, identification of novel effective and selective agents against TNBC is essential. Methods: We used epoxyazadiradione to assess the cell viability, mitochondrial potential, ROS level, cell migration, apoptosis and protein expression in cell culture models of TNBC MDA-MB-231 and ER+MCF-7 breast cancer cells. The molecular mechanism was examined in two different type of breast cancer cells in response to epoxyazadiradione. We have also analyzed the effect of epoxyazadiradione on breast tumor growth using in vivo mice model. Results: In this study, we for the first time investigated that out of 10 major limonoids isolated from Azadirachta indica, epoxyazadiradione exhibits most potent anti-cancer activity in both TNBC and ER+breast cancer cells. Epoxyazadiradione induces apoptosis and inhibits PI3K/Akt-mediated mitochondrial potential, cell viability, migration and angiogenesis. It also inhibits the expression of pro-angiogenic and pro-metastatic genes such as Cox2, OPN, VEGF and MMP-9 in these cells. Furthermore, epoxyazadiradione attenuates PI3K/Akt- mediated AP-1 activation. Our in vivo data revealed that epoxyazadiradione suppresses breast tumor growth and angiogenesis in orthotopic NOD/SCID mice model. Conclusion: Our findings demonstrate that epoxyazadiradione inhibits PI3K/Akt-dependent mitochondrial depolarisation, induces apoptosis and attenuates cell migration, angiogenesis and breast tumor growth suggesting that this compound may act as a potent therapeutic agent for the management of breast cancer.
Keywords: Angiogenesis; Apoptosis; Breast cancer; Limonoids; Metastasis; PI3K

Total synthesis of a hypothetical macroketone of migrastatin - Choudhury, Rahul; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2021)
Danishefsky's macroketone, a simplified analogue of natural product Migrastatin, is one of the lead compounds with potent cancer cell migration inhibition potential. Different biological assays suggest fascin protein as the potential target. Although it was indicated through X-ray co-crystallography where the concerned macroketone analogue was found to bind in the actin-binding sites of fascin, there was a structural discrepancy, as the X-ray co-crystal structure suggested an E-olefin along with inversion of methyl stereochemistry from that of Danishefsky's macroketone. Here, we have accomplished the total synthesis of the `hypothetical macroketone' for the first time. The TiCl4 mediated vinylogous Mukaiyama aldol reaction is the key step in present synthesis.
Keywords: Hypothetical mecroketon; Metastasis; Migrastatin; RCM; vinylogous Mukaiyama aldol reaction (VMAR)

Unbiased phenotype-based screen identifies therapeutic agents selective for metastatic prostate cancer - Chung, Ivy; Zhou, Kun; Barrows, Courtney; Banyard, Jacqueline; Wilson, Arianne; Rummel, Nathan; Mizokami, Atsushi; Basu, Sudipta; Sengupta, Poulomi; Shaikh, Badaruddin; Sengupta, Shiladitya; Bielenberg, Diane R.; et al. (Frontiers in Oncology, 2021)
In American men, prostate cancer is the second leading cause of cancer-related death. Dissemination of prostate cancer cells to distant organs significantly worsens patients' prognosis, and currently there are no effective treatment options that can cure advanced-stage prostate cancer. In an effort to identify compounds selective for metastatic prostate cancer cells over benign prostate cancer cells or normal prostate epithelial cells, we applied a phenotype-based in vitro drug screening method utilizing multiple prostate cancer cell lines to test 1,120 different compounds from a commercial drug library. Top drug candidates were then examined in multiple mouse xenograft models including subcutaneous tumor growth, experimental lung metastasis, and experimental bone metastasis assays. A subset of compounds including fenbendazole, fluspirilene, clofazimine, niclosamide, and suloctidil showed preferential cytotoxicity and apoptosis towards metastatic prostate cancer cells in vitro and in vivo. The bioavailability of the most discerning agents, especially fenbendazole and albendazole, was improved by formulating as micelles or nanoparticles. The enhanced forms of fenbendazole and albendazole significantly prolonged survival in mice bearing metastases, and albendazole-treated mice displayed significantly longer median survival times than paclitaxel-treated mice. Importantly, these drugs effectively targeted taxane-resistant tumors and bone metastases - two common clinical conditions in patients with aggressive prostate cancer. In summary, we find that metastatic prostate tumor cells differ from benign prostate tumor cells in their sensitivity to certain drug classes. Taken together, our results strongly suggest that albendazole, an anthelmintic medication, may represent a potential adjuvant or neoadjuvant to standard therapy in the treatment of disseminated prostate cancer.
Keywords: bone; carcinoma; drug-screen; Metastasis; Prostate